A novel lanthanum strontium cobalt iron composite membrane synthesised through beneficial phase reaction for oxygen separation. Issue 15 (15th October 2019) - Han, Ning; Chen, Ruofei; Chang, Tieyan; Li, Liqing; Wang, Haijiang; Zeng, Lin
Abstract: Composite ceramic membrane is one of the most attractive concepts which combines the advantages of different phases into a single membrane matrix. Recently, the reported significant increased oxygen surface kinetics on the Perovskite/Ruddlesden-Popper composite system because of the formation of novel and fast oxygen transport paths along the hetero-interface has been implanted into the oxygen permeation membrane system. In this work, a novel La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ -(La0.5 Sr0.5 )2 CoO4+δ (LSCF-LSC) composite hollow fiber membrane is synthesized with oxygen permeation flux of 4.52 mL min −1 cm −2 at 950 °C. It presents round 4 times and 2.3 times of that of the single LSCF membrane and LSC-coated LSCF membrane at 900 °C. For better comparison, (La0.576 Sr0.424 )1.136 Co0.3 Fe0.7 O3-δ (LSCF-new) is prepared based on the composition of LSCF-LSC composite. The enhanced oxygen permeability was further investigated through electrochemical impedance spectroscopy (EIS) measurements. We also confirm that LSCF-LSC shows significantly lower area specific resistance (ASRs) for LSCF-LSC|Ce0.8 Sm0.2 O1.9 (SDC)|LSCF-LSC symmetrical cell relative to other symmetrical cells. This novel LSCF-LSC composite membrane also presents high CO2 tolerance, with stable oxygen permeation fluxes round 2.6 mL min −1 cm −2 at 900 °C for 100 h.